Analisis Nilai Pendidikan Moral dalam Cerita Rakyat Putri Pinang Masak Karya Afrizal Cik - Sabrina, Dian; Shomary, Sudirman (UIR Press, 2024)
In folklore there are moral educational value which refers to three dimensions named responsibility, conscience and obligation. The problem in this research is: what are the moral educational value that related to the dimensions of responsibility, conscience and obligation in Putri Pinang Masak folklore by Afrizal Cik and the relation to educational realm of Bloom's Taxonomy? The aim of this research is to describe and analyze data regarding the moral values of education related to responsibility, conscience and obligation and the relation to educational realm of Bloom's Taxonomy contained in Putri Pinang Masak folklore by Afrizal Cik. The theory for this research is Salam’s theory. This research is included in qualitative research with descriptive methods. The data collection technique in this research is a hermeneutic technique. The results of this research found moral educational value in dimension of responsibility, which can be seen from the tireless attitude of a young man in searching for the whereabouts of his family. There are moral educational value in dimension of conscience, which can be seen from the attitude of Juragan Tiung who decided to stop by his ship for safety. There are on the moral educational value of the obligation dimension, which can be seen from the attitude of all the ship's sailors who always say prayers and give thanks.